Konstruksi Kurikulum Pesantren dalam Pendekatan, Model dan Metode Pembelajaran - suheri suheri (JP : JURNAL PENDIDIKAN, 2017)
This paper discusses the construction of curriculum in Islamic boarding school, either in the perspective of approach, the model of fund or learning method. As far as we know that the modernization trend of education in Indonesia has penetrated the idea of modernization of Islamic education in Islamic boarding school, it is undeniable that the presence of Islamic boarding school is open and adopts the development of Islamic boarding school technology, design, model and method of learning. This ultimately affects the dynamics of science in Islamic boarding school environments. The idea of modernization of Islam that found its momentum since the early 20th century Masehi, on the field of education is realized with the establishment of modern educational institutions. So, the traditional of Islamic boarding school (Salaf) transformed into the modern Islamic boarding school (khalaf), of course by deconstructing the existing curriculum. In certain cases, however, the modernization of education has proven to have a positive impact on the development of Islamic boarding school. Not a few the Islamic boarding school eventually able to develop the potential of education and development potential of surrounding communities, and not least the entry of new approaches, models and teaching methods forced Islamic boarding school to reconstruct curriculum design that has been adopted, even forced to abandon the original model and learning of Islamic boarding school.Keywords: Islamic boarding school, curriculum, Instruction